Islamic savings deposit product: a comparison between Kuwait Finance House (M) Berhad and other local Islamic banks in Malaysia / Syed Muhammad Redha Syed Ismail - Syed Ismail, Syed Muhammad Redha (2009)
This report paper is mainly to study on Islamic savings deposit product: a comparison between Kuwait Finance House (M) Berhad and other local islamic banks in Malaysia. Throughout this case study paper, we will analyze and compare between the hybrid Islamic finance contract which refers to the combination of Mudharabah Mutlaqah and Qardh to the existing single contract used, namely Wadiah Yad Dhamanah and Mudharabah which applies for savings deposit products. The difference between a hybrid contracts offered by KFHMB with other local Islamic banks are the Syariah concept used for the contract, profit payment method and the loss incurred by both parties. This paper will also analyze the profit computation for the contracts used in calculating the savings profit distribution. It is found that the profit offered by KFHMB for their savings deposit facility higher than industry backed by their hybrid contracts. The loss incurred by customer can also be reduced based on the sharing ratio of a hybrid contract. The most significant of this paper is where the ideas generated, recommendation and justification part, where the most important information will be disclosed and share to prove the paper’s originality and value to benefits KFHMB, future references and academic purposes.